Evaluation of customized peripheral sealing device acceptance for surgical/medical masks among dental professionals during early COVID-19 pandemic = Evaluación de la aceptación de dispositivos de sellado periférico personalizados para máscaras quirúrgicas/médicas entre dentistas durante la pandemia temprana de COVID-19 - Roque Torres, Gina Delia; Kim, Jessica; Dantas Costa, Eliana; Oyoyo, Udochukwu (2022)
A 3-dimensional (3D) printed custom-frame can improve the peripheral seal of readily available surgical/medical masks. This study aimed to assess the acceptance of a 3D-printed custom-frame with the American Society for Testing and Materials (ASTM) surgical/medical masks and the use of a face shield. A total of 206 subjects from a dental school participated, who answered a multiple-choice questionnaire. Participants received an invitation through the institutional email of the school via Qualtrics platform. 3D printed custom-frames were fabricated for each participant. According to their response, participants were divided into 4 groups: mask only (M), mask and frame (MF), mask and face shield (MFS), and all 3 personal protective equipment (MFFS). Data was analyzed in absolute and relative frequency. The acceptance of a 3D-printed custom-frame in the group MFFS varied between "poor"/''very poor" (44.7%). It allowed "good" performance of routine procedures (40.3%), but "poor" visual quality (48.1%). Musculoskeletal tolerance and ease to perform movements were adequate. There was no interference in olfactory sensitivity (44.7%) or in the ability to breathe (34.5%). Finally, it showed "moderate pain" (48.1%) on the ear and "no pain" (38.9%) on the head. The 3D-printed custom-frame adapted to ASTM surgical/medical face masks showed reasonable tolerance. Side effects of ear pain ranging in degrees were noted. Further research is indicated to evaluate safety, comfort, compliance, side effects, and occupational hazards of long-term use of enhanced PPE recommendations.Avoiding the recurrent outbreaks of COVID-19, the use of PPE by the public is necessary. Improper PPE use is a major source of concern for human and environmental health. Preventing such activities can be done by following steps involved in PPE disposals or by getting a new way to re-use such as improving peripherical sealing. Our work highlights that a custom-frame can improve...
El sellado periférico de las máscaras médicas/quirúrgicas puede ser mejorado fácilmente mediante un marco personalizado impreso en 3 dimensiones (3D). Este estudio tuvo como objetivo evaluar la aceptación de un marco personalizado impreso en 3D cuando usado en combinacion con máscaras médicas/quirúrgicas de la Sociedad Estadounidense para Pruebas y Materiales (ASTM) asi como con el uso de protector facial. Participaron un total de 206 sujetos de una facultad de odontología, quienes respondieron un cuestionario de opción múltiple. Los participantes recibieron una invitación a través del correo institucional de la escuela a través de la plataforma Qualtrics. Se fabricaron marcos personalizados impresos en 3D para cada participante. Según su respuesta, los participantes se dividieron en 4 grupos: solo máscara (M), máscara y marco (MF), máscara y protector facial (MFS) y los 3 equipos de protección personal (MFFS). Los datos se analizaron en frecuencia absoluta y relativa. La aceptación de un marco personalizado impreso en 3D en el grupo MFFS varió entre "pobre"/''muy pobre" (44,7%). Permitió un "buen" desempeño de los procedimientos de rutina (40,3%), pero una "mala" calidad visual (48,1%). La tolerancia musculoesquelética y la facilidad para realizar movimientos fueron adecuadas. No hubo interferencia en la sensibilidad olfativa (44,7%) ni en la capacidad de respirar (34,5%). Finalmente, mostró "dolor moderado" (48,1%) en el oído y "sin dolor" (38,9%) en la cabeza. El marco personalizado impreso en 3D adaptado a las máscaras faciales quirúrgicas/médicas de ASTM mostró una tolerancia razonable. Se observaron efectos secundarios de dolor de oído que variaron en grados. Estudios futuros deben evaluar la seguridad, la comodidad, efectos secundarios y los riesgos laborales del uso a largo plazo para este tipo de combinación. Para evitar los brotes recurrentes de COVID-19, es necesario el uso de equipamiento...
En revista Odóvtos, vol. 24, no. 3 (septiembre-diciembre 2022)
Descripción basada en el contenido visto el 05 de diciembre, 2024
También disponible en formato HTML y EPUB